The modelling of processing conditions for polypropylene-nanoclay integral hinges at high heat exposure - Othman, Mohd Hilmi (2015)
This research is about generating models of injection moulding processing conditions, towards quality performance of polypropylene-nanoclay integral hinges, exposed to high heat temperature. The assessment of hinges’ quality performance analyses was translated as the signal to noise ratio values for ultimate tensile strength, shrinkage and warpage. This research had adopted Taguchi Optimisation Method, to optimise the processing conditions, to generate the regression models and to construct master curves for quality performance prediction based on nanoclay content. According to the results, 18 regression models have been successfully generated. 3 types of master curves have been constructed based on the produced models with the specific nanoclay content. Additionally, the quality performance of the integral hinges was extended to high heat exposures, and the additional of nanoclay had produced a significant advancement in the injected mould samples. Validation test has been carried out towards the regression model with most of the models have produced good predictions of quality performances. The novelty of this research is the correlations between the optimum injection moulding processing conditions with the precise range of shrinkage, warpage and ultimate tensile strength. The correlations were simplified in the form of regression models and master curves. These models and master curves were recommended as references and a prediction method, specifically for polypropylene-nanoclay integral hinges manufacturing and design process. These findings will lead to wider and optimum applications of thin layer parts and components such as packaging products; as well as other manufacturing field such as artificial human parts development and building appliances.